Monitoring and evaluation of the interaction between deoxynivalenol and gut microbiota in Wistar rats by mass spectrometry-based metabolomics and next-generation sequencing. (November 2018) - Miró-Abella, Eugènia; Torrell, Helena; Herrero, Pol; Canela, Núria; Arola, Lluís; Borrull, Francesc; Ras, Rosa; Fontanals, Núria
Abstract: Published evidence has demonstrated the several toxic characteristics of mycotoxins and their considerable risk to human and animal health. One of the most common uncertainties regards whether if very low concentrations of the mycotoxin deoxynivalenol (DON), easily consumed within the Mediterranean Diet, can cause metabolic alterations; some of them produced by the interaction between DON and gut microbiota. Accordingly, faecal samples were collected from Wistar rats that had consumed the mycotoxin DON at low levels (60 and 120 μg kg -1 body weight of DON per day), and were analysed by ultra-high performance liquid chromatography coupled with tandem mass spectrometry detection, in order to monitor the mycotoxin DON and its metabolite de-epoxy deoxynivalenol (DOM-1). The obtained results showed an evolution in DON excretion and the metabolite DOM-1 which has less toxic properties, over the course of the days of the study. To elucidate whether intestinal microbiota had a role in the observed detoxification process, the changes in microbial gut biodiversity were explored through 16s rRNA high throughput sequencing. No main changes were detected but significant increase in Coprococcus genus relative abundance was found. Further studies are needed to confirm if intestinal microbiota composition and function are affected by low mycotoxin concentrations. Highlights: For the first time a metagenomic study assesses the response of gut microbial composition to DON administration. An increase of the excretion of DOM-1 in faecal samples was observed along the several weeks of DON consumption. A significant increase in the relative abundance of the Coprococcus genus was observed in the gut after the DON consumption.